Arabidopsis Sec1/Munc18 Protein SEC11 Is a Competitive and Dynamic Modulator of SNARE Binding and SYP121-Dependent Vesicle Traffic([W])([OA]) - Karnik, Rucha (American Society of Plant Biologists, 2013)
The Arabidopsis thaliana Qa-SNARE SYP121 (=SYR1/PEN1) drives vesicle traffic at the plasma membrane of cells throughout the vegetative plant. It facilitates responses to drought, to the water stress hormone abscisic acid, and to pathogen attack, and it is essential for recovery from so-called programmed stomatal closure. How SYP121-mediated traffic is regulated is largely unknown, although it is thought to depend on formation of a fusion-competent SNARE core complex with the cognate partners VAMP721 and SNAP33. Like SYP121, the Arabidopsis Sec1/Munc18 protein SEC11 (=KEULE) is expressed throughout the vegetative plant. We find that SEC11 binds directly with SYP121 both in vitro and in vivo to affect secretory traffic. Binding occurs through two distinct modes, one requiring only SEC11 and SYP121 and the second dependent on assembly of a complex with VAMP721 and SNAP33. SEC11 competes dynamically for SYP121 binding with SNAP33 and VAMP721, and this competition is predicated by SEC11 association with the N terminus of SYP121. These and additional data are consistent with a model in which SYP121-mediated vesicle fusion is regulated by an unusual “handshaking” mechanism of concerted SEC11 debinding and rebinding. They also implicate one or more factors that alter or disrupt SEC11 association with the SYP121 N terminus as an early step initiating SNARE complex formation.